Involvement of CD95/Apo1/Fas in cell death after myocardial ischemia - Jeremias, Irmela; Kupatt, Christian; Martín-Villalba, Ana; Habazettl, H.; Schenkel, Johannes; Boekstegers, Philipp Tjarko; Debatin, Klaus-Michael (Circulation, 2000)
Background: The death of cardiac cells during ischemia and reperfusion is partially mediated by apoptosis, as seen, eg, in autopsy material of patients after acute myocardial infarction.Methods and Results: To study the role of CD95/Fas/Apo1 for induction of postischemic cell death, we used an ischemia/reperfusion model of isolated rat and mouse hearts in Langendorff perfusion. In this model, caspase-dependent apoptosis occurred during postischemic reperfusion. Moreover, soluble CD95 ligand/Fas ligand was released by the postischemic hearts early after the onset of reperfusion. In addition, this ligand was synthesized de novo under these circumstances. Similar findings were observed for other “death-inducing” ligands, such as tumor necrosis factor (TNF)-α and TNF-related apoptosis-inducing ligand. In primary adult rat myocyte culture, hypoxia and reoxygenation caused a marked increase in sensitivity to the apoptotic effects of CD95 ligand. Isolated hearts from mice lacking functional CD95 (lpr) display marked reduction in cell death after ischemia and reperfusion compared with wild-type controls.Conclusions—These data suggest that CD95/Apo1/Fas is directly involved in cell death after myocardial ischemia. The CD95 system might thus represent a novel target for therapeutic prevention of postischemic cell death in the heart.